Prevalence of associated injuries of spinal trauma and their effect on medical utilization among hospitalized adult subjects - a nationwide data-based study - Chou Pesus; Lin Ching-Heng; Lee Yi-Hui; Chu Dachen; Yang Nan-Ping (BMC, 2009)
Abstract Background This study was wanted to investigate the prevalence of concomitant injuries among hospitalized acute spinal trauma patients aged 20 and over and the effects of those injuries on medical utilization in Taiwan. Methods Nationwide inpatient datasets of Taiwan's National Health Insurance (NHI) database from between 2000 and 2003 were used. The major inclusion criteria used to select cases admitted due to acute spinal trauma were based on three diagnostic International Classification of Disease, 9th Version (ICD-9) codes items: (1) fracture of vertebral column without mention of spinal cord injury; (2) fracture of vertebral column with spinal cord injury; or (3) spinal cord lesion without evidence of spinal bone injury. To investigate the associated injuries among the eligible subjects, the concomitant ICD-9 diagnosis codes were evaluated and classified into six co-injury categories: (1) head trauma; (2) chest trauma; (3) abdominal trauma; (4) pelvic trauma; (5) upper extremities trauma; (6) lower extremities trauma. Results There were 51,641 cases studied; 27.6% of these subjects suffered from neurological deficit, but only 17.3% underwent a surgical procedure for spinal injury. Among them, the prevalence of associated injuries were as follows: head trauma, 17.2%; chest injury, 2.9%; abdominal trauma, 1.5%; pelvic injury or fracture, 2.5%; upper limb fracture, 4.4%; lower limb fracture, 5.9%. The three major locations of acute spinal injury (cervical, thoracic, or lumbar spine) were found to be combined with unequal distributions of associated injuries. By stepwise multiple linear regression, gender, age, location of spinal injury, neurological deficit, surgical intervention and the six combined injuries were identified significantly as associated factors of the two kinds of medical utilization, length of stay (LOS) and direct medical cost. The combinations of acute spinal trauma with lower extremity injury, pelvic injury, chest injury, abdominal injury and upper extremity injury resulted in of the highest utilization of medical resources, the estimated additional LOS being between 4.3 and 1.2 days, and the extra medical cost calculated as being between $1,230 and $320. Conclusion The occurrence of associated Injuries among hospitalized acute spinal trauma patients in Taiwan is not uncommon, and results in an obvious effect on medical utilization.